Peran Kepala Sekolah Terhadap Kinerja Guru dalam Meningkatkan Mutu Pendidikan di SDK Ona Nangahure - Lukas Bera (Peneliti.net, 2021)
This study aims to: 1) describe the role of the principal on teacher performance in improving the quality of education at SDK Ona Nangahure. The research used was descriptive qualitative research. Data collection techniques were carried out through interviews, observation and documentation. Test the validity of the data used in this study, namely research using source triangulation. Miles and Huberman's data analysis techniques start from the data collection stage, the reduction stage, data display, and verification/conclusion. The results showed that the role of the Principal of SDK Ona Nangahure on teacher performance was that the principal always controlled each teacher during the learning process so as to produce quality education. Obstacles faced by principals in improving teacher performance at the Ona Nangahure SDK are the lack of teacher discipline in entering school and teacher delays in submitting learning tools. Efforts made by the principal in improving teacher performance at the Ona Nanaghure SDK are always, providing motivation and encouragement to subordinates so that they work well, based on the results of the study it can be concluded that the principal's role on teacher performance in improving the quality of education at the Ona Nangahure SDK is that the principal the school always controls the teacher in the learning process